1985
DOI: 10.1007/bf00790029
|View full text |Cite
|
Sign up to set email alerts
|

The function of host discrimination and superparasitization in parasitoids

Abstract: Host discrimination, i.e. the ability to distinguish unparasitized hosts from parasitized ones, and to reject the latter for egg laying is present in many parasitic wasp species. This property is classically considered as an example of contest competition, and is supposed to have a number of functions. However, different species do not react to each other's marks and lay eggs in hosts parasitized by the other species. Apparently the marks used for recognition are specific.Multiparasitization is the best strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
2
7

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 16 publications
1
82
2
7
Order By: Relevance
“…This latter function is advantageous to the first wasp because otherwise, when conspecifics search the area later and superparasitize hosts parasitized by the first female, it could lose offspring via larval competition. However, the probability that a second clutch will win the competition with a first clutch decreases over time (Bakker et al 1985;Pijls et al 1990;Visser et al 1992b). Hence, the profitability of the mark decreases over time for both functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter function is advantageous to the first wasp because otherwise, when conspecifics search the area later and superparasitize hosts parasitized by the first female, it could lose offspring via larval competition. However, the probability that a second clutch will win the competition with a first clutch decreases over time (Bakker et al 1985;Pijls et al 1990;Visser et al 1992b). Hence, the profitability of the mark decreases over time for both functions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in E. lopezi, it can be optimal to lay more than one egg in a host; this raises the question o f why these eggs are not laid at the first oviposition, instead of at successive encounters? It has been found that the first egg laid in a host has a higher probability o f winning in competition with eggs laid later in the host (Bakker et al 1985;Pijls et al 1990;Visser et al 1992b). Therefore it can be beneficial to search first for unparasitized hosts, instead o f using time to lay further eggs in a host.…”
Section: Discussionmentioning
confidence: 99%
“…The issue has only occasionally been considered. On the basis of simulation models that assumed costs of discrimination in terms of missed opportunities to lay eggs, Turlings et al (1985) concluded that interspecific host discrimination was unlikely to arise de novo, because such discrimination is disadvantageous to the first species to evolve to avoid multiparasitism (see also Bakker et al, 1985).…”
Section: Mps and Interspecific Discriminationmentioning
confidence: 99%
“…Female parasitoids face both physiological (egg load, life expectancy, movement capacity, experience, ability to learn) (van Alphen and Visser 1990 and references therein) and environmental constraints (presence or absence of competitors, distribution and density of hosts, level of host patch exploitation) (Bakker et al 1985;Hubbard et al 1987;Visser et al 1990), and superparasitism may be the optimal behavior to maximize ®tness gain under certain combinations of these factors. Even if host-seeking larvae can discriminate between unparasitized hosts and hosts parasitized by conspeci®cs, we may expect that constraints such as movement capacity, life expectancy and environmental factors will also aect superparasitism decisions by these larvae.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of female parasitoids to distinguish parasitized from unparasitized hosts is called host discrimination (Roitberg and Mangel 1988). Host discrimination has a strong selective advantage because females can avoid wasting eggs and time when rejecting a parasitized host is faster than ovipositing (Bakker et al 1985). Intraspeci®c host discrimination (the ability to recognize hosts parasitized by conspeci®cs) is common in hymenopteran parasitoids ( van Lenteren 1981; van Alphen and Visser 1990) and rare in dipteran parasitoids ( van Lenteren 1981;Feener and Brown 1997), having been recorded in only two tachinid species (Lo pez et al 1995).…”
Section: Introductionmentioning
confidence: 99%